2018
DOI: 10.1016/j.hjc.2017.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcome in women with congenital heart disease: A single-center experience

Abstract: Pregnancies in ACHD patients are at high risk for complications. Advanced modified WHO class, prior medication use, and high BMI were related to adverse cardiac events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 21 publications
0
36
0
3
Order By: Relevance
“…7 In the cases of uncorrected septal defects, especially right-to-left shunt or bidirectional shunt, PH is a threatening condition that increases maternal mortality. [2][3][4]7 Due to improvement in peripartum management involving multidisciplinary teams and availability of PH-specific medication, the maternal mortality in pregnant women with CHD-PH is reduced as low as 3.8%. 2 However, in our hospital registry, the maternal mortality rate among pregnant patients with CHD-PH was still high.…”
Section: Discussionmentioning
confidence: 99%
“…7 In the cases of uncorrected septal defects, especially right-to-left shunt or bidirectional shunt, PH is a threatening condition that increases maternal mortality. [2][3][4]7 Due to improvement in peripartum management involving multidisciplinary teams and availability of PH-specific medication, the maternal mortality in pregnant women with CHD-PH is reduced as low as 3.8%. 2 However, in our hospital registry, the maternal mortality rate among pregnant patients with CHD-PH was still high.…”
Section: Discussionmentioning
confidence: 99%
“…6 Although pregnancy is often tolerated and well managed in women with ACHD, 7 a systematic review involving 2491 pregnancies in women with ACHD 8 found that adverse maternal, obstetric, and neonatal events occur at a higher rate than in the general obstetric population. 9,10…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have demonstrated increased obstetric and neonatal risks for women with ACHD, most only included patients seen in tertiary care centers, 7,9,10,11,13,16,17 combined women with structural and acquired heart disease, 11,13,14,15 or lacked a control group. 7,9,10,11,14,16,17 In Canada, only 23% of patients with ACHD are regularly followed up by physicians at a specialized ACHD clinic; therefore, previous studies may not be generalizable to current practice. 18 In addition, previous studies have lacked the power to examine outcomes by ACHD subtype to determine whether all patients are uniformly at increased risk of adverse obstetric or neonatal outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…9 Interestingly, in more than a third of the cohort the establishment of PAH-CHD diagnosis occurred during pregnancy, which was also a finding in previous studies. 10,11 Notably, some of the patients were referred late in their pregnancies as emergencies in the tertiary centre. 8 In total, 6.4% of pregnant women died, 35.1% developed heart failure and 10.6% experienced a pulmonary hypertension crisis.…”
Section: Despoina Ntiloudi and George Giannakoulasmentioning
confidence: 99%